Increased Range of Motion and Function in an Individual with Breast Cancer and Necrotizing Fasciitis—Manual Therapy and Pulsed Short-Wave Diathermy Treatment. (5th July 2010) - Johnson, Wayne; Draper, David O.
Abstract : Necrotizing fasciitis is a severe soft tissue infection of the subcutaneous tissue and fascia affecting those predisposed to immune system compromise. It is a life threatening condition; mortality can be reduced by rapid diagnosis, adequate early surgical debridement and antibiotic ointment. In this case report we present the use of manual therapy (MT) techniques, joint and soft tissue mobilization, following a regimen of pulsed short wave diathermy (PSWD) in the treatment of a woman 3 years post necrotizing fasciitis developed during chemotherapy treatment for breast cancer. During her course of chemotherapy, she developed necrotizing fasciitis which was treated with extensive surgical debridement (8 linear feet of incisions) followed by debridement to both hips and the pelvis area. When we started working with her, we put her on a course of PSWD/MT. After six weeks of following this regimen, she gained25 ° of external rotation in both her left and right hips, 15 ° of left hip flexion and17 ° of right hip flexion. The patient gained10 ° of right hip extension, yet there was no improvement in left hip extension. The treatments led to a dramatic reduction in pain and scarring from previous surgeries. The patient also returned to running.